The relationship between psychological variables with job satisfaction among couples in stable relationships - Kgantsi, Tselane Rose (My University, 2006)
There is scant evidence of the links between job satisfaction and variables such as gender, age and occupational status among black people, especially in relation to work-family balance. Therefore this study will focus on the relationship between job satisfaction and its predictors namely; gender, job status, age, marital satisfaction, overall satisfaction with life and psychological well-being. A survey research design was employed in this study with a cross-sectional approach informing the design. A systematic random sample of a 100 people working in organizational institutions was used in this article. Different employment sectors were randomly selected for example government, parastatal, private business. In addition different levels of employees from middle management, junior staff and top management were also selected. The findings indicated that the level of job satisfaction is moderate to high for both male and female (43% male & 45% female). Older employees on the other hand have shown moderate levels of job satisfaction. The relationship between job satisfaction and job status yielded moderate results across all levels of work. The findings indicate that the level of job satisfaction is not specifically in relation to gender. In this article, it has been found that the majority of the participants who are satisfied with their jobs are older employees. Job status does not seem to have a significant importance towards job status because the high the job status, the high the level of job satisfaction. General belief is that women will have lower job satisfaction as compared to men. Organisations need to diffuse the myth that there is a difference in the level of job satisfaction. In many studies that have been conducted, it has been found that age is a good determiner of job satisfaction. The main finding is that older employees are more likely to cognitively justify remaining in the organisation because they are more likely to posses more traditional values and supportive work ethics. It is therefore recommended that organisations render ample training to younger employees
M.Soc.Sc (Research Psychology) North-West University, Mafikeng Campus, 2006
Keywords: Job satisfaction